Влияние окисленной нефтеполимерной смолы на свойства криогелей; Химия в интересах устойчивого развития; Т. 27, № 2 - Алтунина Л. К. Любовь Константиновна; Фуфаева М. С. Мария Сергеевна; Манжай В. Н. Владимир Николаевич; Бондалетов В. Г. Владимир Григорьевич; Фисенко Д. В. Дарья Викторовна (2019, 2019)
Заглавие с экрана